Regional head corruption and industrial growth: Evidence from Mojokerto Regency and City - Sanda Aditiya Arsandi (Integritas: Jurnal Antikorupsi, 2022)
There is a difference of opinion amongst experts regarding the impact of corruption on industrial growth. Many people believe that corruption will hinder industrial growth, but several studies (especially in Asia) have found that corruption is the grease for the wheel of business. This study seeks to examine the relationship between business and corruption by using case study methods and quantitative content analysis techniques on conditions in Mojokerto Regency and City, two regions in which industry is an important development sector. In the last four periods, the former Regent and Mayor of Mojokerto have been reported as being involved in corruption cases. Using secondary data from Badan Pusat Statistik, we examine the relationship between corrupt governments in the Regency and City of Mojokerto on industrial growth using secondary data from Badan Pusat Statistik (BPS). By using quantitative analysis on several parameters of industry growth (such as the number of workers, investment value, number of firms and number of products), we find that the regional heads who were involved in several corruption cases in both Mojokerto Regency and Mojokerto City could not bring about positive change in industrial growth during their tenure, instead overseeing some decline in both regions.